Collaborative Urban Transformations - Adaptive Planning in Trento - Marzetti, Francesca (Università degli studi di Trento, 2021)
The contemporary cities are facing affected by three factors that are changing our lifestyle: the economic and relative social crisis getting worse by the pandemic, the technological revolution and the climate changes effects. In this framework, this thesis investigates the adaptive urban planning as a part of DICAM - Trento Urban Transformation Research Programme, which started in 2017 to provide scientific support for the Trento general urban plan review. This doctoral research aims to demonstrate how the open, adaptive and metabolic plan can respond to city demands by means of Collaborative urban Transformations: the processes that go beyond the dichotomous relationship between the strategical approach and the tactical one. The thesis output is an Open Toolbox made of strategies, tactics and devices to catalyses the challenges, goals and actions of adaptive urban plan, as the Trento Leaf Plan proposed by the TUT research group. The final Manifesto has been proposed to test and implement in other contexts the new planning approach capable to activating the ecological transition, as an adaptive, multi-scalar and interdisciplinary process that leads towards a city more ECO, ACCOGLIENTE, ACCESSIBILE, SMART and BELLA.